Progressive collapse of reinforced concrete buildings considering flexure-axial-shear interaction in plastic hinges. Issue 1 (1st January 2021) - Abdulsalam, Meshal A.; Chaudhary, Muhammad Tariq A.
Abstract: Progressive collapse assessment of a reinforced concrete (RC) building designed only for gravity loads and lacking a dedicated lateral load resisting system was carried out using the alternate load path (ALP) method and finite element method (FEM) numerical model created in software SAP2000. Plastic hinge capacity of the members was evaluated considering flexure (M), axial force (N) and shear force (V) interaction and a validated procedure was devised to incorporate the plastic hinge capacity based on M-N-V interaction into the results obtained from the FEM model. It was found that consideration of M-N-V interaction resulted in plastic hinge capacities that were lower than the flexure-only capacity of the plastic hinges available in the FEM software which caused the progressive collapse to initiate at a lower load and also resulted in increased collapse area. In the second part of the study, it was demonstrated that the progressive collapse resistance of the building for the interior and the edge column removal scenarios was appreciably improved after ordinary moment frames were cost-effectively designed at selected locations without increasing member cross-sectional dimensions. However, key element design concept approach was needed for improving the progressive collapse performance for the corner column loss scenarios. Relative reduction in the plastic hinge capacity due to M-N-V interaction as compared to flexure-only hinge capacity was found to be lower for the redesigned building due to improved member capacity.